The Activities of Local Government Bodies to Improve the Sanitary Condition of Cities in Western Siberia (Late XIX — Early XX Centuries) - A. I. Tatarnikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The activities of local authorities in the sanitary improvement of cities in the West Siberian region are characterized in the article. The author analyzes the sanitary regulations of the self-government bodies addressed to the urban population, identifies their common and distinctive features. Attention is focused on the problem of compliance with the instructions issued by the authorities by the owners of factories, plants, trade shops, public baths, hairdressers and other institutions of urban infrastructure, as well as ordinary citizens. Methods of punishment for violation of the accepted sanitary rules and the effectiveness of their application are considered. The conclusion is made about the intensification of the work of urban self-government bodies in ensuring sanitary order, which was caused by an increase in the rates of economic development of cities, an increase in their population, an acceleration of migration processes and, as a consequence, an unfavorable epidemiological situation, an expansion of the residential area due to the chaotic development of urban outskirts, pollution of water supply sources, the emergence of unauthorized household waste dumps. It is emphasized that the need to solve the problems of sanitary improvement forces the city authorities to seek support from caring citizens, to establish interaction with them, which brings first positive results, contributes to the development of private initiative in improving the sanitary condition of the city economy and residential yards of ordinary inhabitants.